2019
DOI: 10.1039/c9nj04775a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structures, and optical and magnetic properties of free-base tetrapyrazinoporphyrazine in various reduction states

Abstract: The synthesis, and spectral and structural characterization of the novel radical anion and dianion salts of free-base tetrapyrazinoporphyrazine (H2TPyzPz) as well as studies of their magnetic properties have been described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…29 Moreover, the singlet ground state for the H 2 TPyzPz 2− dianions was shown by DFT calculations (the singlet–triplet energy gap was calculated to be 1130 K). 29 It should be noted that salt 3 is also EPR silent, indicating the diamagnetism of deprotonated HT(PhnPyz)Pz − anions. This supports the deprotonation of the macrocycle at the formation of 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…29 Moreover, the singlet ground state for the H 2 TPyzPz 2− dianions was shown by DFT calculations (the singlet–triplet energy gap was calculated to be 1130 K). 29 It should be noted that salt 3 is also EPR silent, indicating the diamagnetism of deprotonated HT(PhnPyz)Pz − anions. This supports the deprotonation of the macrocycle at the formation of 3 .…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24][25][26][27] However, till now, only a few anionic compounds have been reported for pyrazine analogues of phthalocyanine, tetrapyrazinoporphyrazines (TPyzPzs). Those obtained and studied are a series of radical anion and dianion salts based on unsubstituted free-base H 2 TPyzPz, 28,29 salts of the macrocycles with acceptor (Cl, CN) substituents, 30 or an extended p-system. 31 Reduction of Fe II TPyzPzEt 8 -iron(II) octaethyltetrapyrazinoporphyrazine -by zinc dust yields crystalline complex based on {Fe II (TPyzPzEt 8 ) 4À } 2À dianions that coordinate two ZnCl 2 units on the periphery of the macrocycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic charge-transfer complexes (CTCs), composed of wellaligned electron donor (D) and acceptor (A), often possess unique physical properties distinguished from the parent molecules, including conductibility, paramagnetism, thermoelectricity, and luminescence [1][2][3] . These fascinating characteristics of CTCs come from their new electronic structure and aggregation state which make them ideal functional materials for optoelectronic devices 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Organic charge-transfer complexes (CTCs), composed of a wellaligned electron donor (D) and acceptor (A), oen possess unique physical properties distinguished from the parent molecules, including conductibility, paramagnetism, thermoelectricity, and luminescence. [1][2][3] These fascinating characteristics of CTCs come from their new electronic structure and aggregation state which make them ideal functional materials for optoelectronic devices. 4,5 Besides, recent advances have demonstrated that CTCs show strong near-infrared (NIR) lightharvesting ability and a good photothermal effect due to the intense charge transfer interaction and activation of nonradiative pathways, which make CTCs one kind of promising NIR-absorbing photothermal agents (PTAs) for antitumor therapy, antibacterial and water desalination.…”
Section: Introductionmentioning
confidence: 99%